Pressure-sensitive in-situ underwater adhesives - Jiabin Liu; Parth Singh; Tsz Hung Wong; Shaoting Lin (Communications Physics)
Abstract While in-situ underwater adhesives are highly desirable for marine exploration and underwater robotics, existing underwater adhesives suffer from significantly reduced performance compared to air-cured adhesives, mainly due to difficulties in removing interfacial water molecules. Here, we develop a pressure-sensitive in-situ underwater adhesive featuring superabsorbent particles infused with functional silane and hydrogel precursors. When injected into an underwater crack, the particles quickly absorb water, swell, and fill the crack. Mechanical pressure is applied to improve particle-particle and particle-substrate interactions, while heat is utilized to trigger thermal polymerization of the hydrogel precursors. This process creates porous adhesives via bulk polymerization and forms covalent bonding with the substrate via surface silanization. Our experiments demonstrate that mechanical pressure significantly enhances the adhesive’s stretchability (from 3 to 5), stiffness (from 37 kPa to 78 kPa), fracture toughness (from 1 kJ/m2 to 7 kJ/m2), and interfacial toughness with glass substrates (from 45 J/m2 to 270 J/m2).